JOURNAL OF LANGUAGE AND LITERATURE WORD TEMPLATE - Firstiyanti, Aulia Haris (Journal of Language and Literature, 2015)
This is a descriptive qualitative research on how English copular clauses in a gothic science fiction novel are translated into Indonesian. The first problem of this research is what kinds of English copular clauses are used by the author, and the second is what kinds of Indonesian clauses are employed in translating them into Indonesian. The researcher chooses the topic since there are no formal correspondence of English copular clauses in Indonesian. The objectives of this research are to classify the English copular clauses used by the author in composing this novel and to identify the kinds of Indonesian clauses employed by the translator. The data are taken from a gothic science fiction novel entitled Frankenstein and its translation. The findings of this research show that, firstly, the predicational clause is the one which is dominantly used by the author to compose this science fiction novel; the precentage of predicational clause is 66%. The second finding is that the translator used two categories of Indonesian clause based on the category of word or phrase which is contributed as predicate to translate English copular clauses. The two categories of Indonesian clauses are noun clause and verb clause; the precentage of noun clause is 10%; on the other hand, the precentage of verb clause is 90%.Keywords: Translation, Indonesian clauses, English copular clause